Studying micro RNA Function and Dysfunction in Alzheimer’s Disease - Lukiw, Walter J.; Andreeva, Tatiana V.; Grigorenko, Anastasia P.; Rogaev, Evgeny I. (Frontiers in Genetics, 2013)
Alzheimer’s disease (AD) is a tragic, progressive, age-related neurological dysfunction, representing one of the most prevalent neurodegenerative disorders in industrialized societies. Globally, 5 million new cases of AD are diagnosed annually, with one new AD case being reported every 7 seconds. Most recently there has been a surge in the study of the regulatory mechanisms of the AD process, and the particular significance of small non-coding 22 ribonucleotide RNAs called micro RNAs (miRNAs). Abundant data have profiled miRNA patterns in healthy, aging brain, in mild cognitive impairment (MCI), and in the moderate- and late-stages of AD. The major mode of action of miRNA is to interact, via base-pair complementarity, with ribonucleotides located within the 3’ un-translated region (3’-UTR) of multiple target messenger RNAs (mRNAs), and in doing so decrease the capability of that specific mRNA to be expressed. Many miRNAs are highly cell- and tissue-specific. The human brain uses a highly specific fraction of all known human miRNAs, and among small non-coding RNAs (sncRNAs). In general, in contrast to normally, aging human brain, in AD a family of pathogenically up-regulated miRNAs appear to be down-regulating the expression certain brain-essential mRNA targets, including key regulatory genes involved interactively in neuroinflammation, synaptogenesis, neurotrophic functions, and amyloiogenesis. These up-regulated, NF-kB-sensitive miRNAs, involved in the innate immune and inflammatory response and synaptic, neurotrophic and amyloidogenic functions include miRNA-9, miRNA-125b, miRNA-146a and miRNA-155. Other miRNAs of the miRNA-15/107 family, miRNA-153 and miRNA-190, and others, will be discussed. Overall, this manuscript will review the known contribution of miRNAs to aging brain function and the role they appear to play in the incidence and progression of AD.